The Uptake of Organic Agriculture: A Decade of Worldwide Development - Paull, John (Journal of Social and Development Sciences, 2011)
It has been claimed that organic agriculture is the fastest growing agriculture based industry in the world. The land devoted to organic agriculture worldwide has increased over the past decade from 15.8 million hectares to 37.2 million hectares exhibiting a compounding rate of growth of 8.9% per annum. This paper disaggregates the global growth in organic agriculture land over the past decade using country as the unit of analysis. For each country, two indices of organics sector growth are derived, firstly, the actual hectares increase, and secondly, the hectares-multiplier, that is the factor by which the organic hectares have changed over the decade. Growth over the past decade is presented for 71 countries which taken together account for 35.3 million organic agricultural hectares, that is 94.8% of the total global organic agriculture area and 58.2% of the total global agriculture area. The analysis reveals that, underlying what appears at the global level to be steady incremental growth over the decade, the growth appears very uneven when disaggregated by country. The decadal increase in organic hectares ranges from Australia’s gain of 4.3 million organic hectares and China’s gain of 1.9 million organic hectares through to Costa Rica’s decrease of 1549 organic hectares. Globally, the organic hectares total has multiplied by 2.3 in the decade from 2001 to 2011, but this has varied greatly by country. Uruguay increased its organic hectares dramatically with a hectares-multiplier of 716.1, and India with a multiplier of 689.7. In contrast, Denmark has barely increased with a hectares-multiplier of 1.07, while Suriname exhibited the greatest shrinkage with a multiplier of 0.03. China and India are the only countries that rank in the top ten countries for both of the indices of organics growth, namely, the decadal organic hectares increase and the decadal organic hectares-multiplier.